Mindfulness Is Associated With Lower Stress and Higher Work Engagement in a Large Sample of MOOC Participants - Bartlett, Larissa; Buscot, Marie-Jeanne; Bindoff, Aidan; Chambers, Richard; Hassed, Craig (Frontiers in Psychology, 2021)
Objective: This study aimed to understand the associations between mindfulness, perceived stress and work engagement in a very large sample of English-speaking adults, from 130 different countries. It also aimed to assess participants’ self-reported changes following a six-week mindfulness massive open online course (MOOC). Methods: Participants in the six-week MOOC were invited to complete pre-post online surveys. Cross-sectional associations were assessed using univariate linear models, followed by structural equation models to test mediation pathways in baseline data (N=16,697). Self-reported changes in mindfulness, stress and engagement following training were assessed using within-group t-tests (n=2,105). Results: Each standard deviation unit increase in mindfulness was associated with a 0.52 standard deviation unit decrease in perceived stress, and with 0.06 standard deviation unit increment in work engagement. 73% of the influence of mindfulness on engagement was direct. Following the mindfulness MOOC, participants reported higher mindfulness (d=1.16), reduced perceived stress (d=1.00) and a small improvement in work engagement (d=0.29). Conclusions: Mindfulness was associated with lower perceived stress and higher work engagement in both cross-sectional and longitudinal analyses. These findings support mindfulness as a potentially protective and modifiable personal resource. The MOOC format offers a low cost, highly accessible means for extending the reach and potential benefits of mindfulness training to large numbers of people.